Assessment of Healthcare Resource Utilization by Anticoagulant Heparinoid Dosage Level in Patients Hospitalized with COVID-19. (November 2022) - Robinson, Keith; Schott, Laura L.; Matthews, Tom; Tyagi, Manu; Ajmani, Vivek B.; Sacco, Nancy; Cao, Zhun
The aim was to describe inpatients with COVID-19 empirically prescribed heparinoid anticoagulants and compare resource utilization between prophylactic/low-dose and therapeutic/high-dose groups.Methods: This retrospective observational study used real-world data from 880 US hospitals in the PINC AI™ Healthcare Database during 4/1/2020–11/30/2020. Descriptive analysis was used to characterize patients. Multivariable regression was used to evaluate intensive care unit (ICU) admissions, length of stay (LOS), mortality, and costs by anticoagulation dose group, adjusting for cohort characteristics. Among 122, 508 inpatients, 29, 225 (23.9%) received therapeutic/high-dose, and 93, 283 (76.1%) received prophylactic/low-dose anticoagulation. The high-dose group had more comorbidities and worse laboratory values compared with low-dose. Respectively, ICU admission rates were 36.7% and 19.1% and LOS median (Q1, Q3) was 8 (5, 15) and 5 (3, 9) days. In separate adjusted models, high-dose anticoagulation was associated with a 45% increase in odds of ICU admission, 26% increase in odds of in-hospital mortality, 21% longer average LOS, and 28% greater average total cost compared with low-dose (each P < 0.001). Prophylactic/low-dose anticoagulation treatment was associated with decreased healthcare resource utilization (HRU) in hospitalized patients with COVID-19.